A high-dispersion wood-plastic thermoplastic polyurethane elastomer material and preparation method thereof
By using strong polar branched polyolefin additives in wood-plastic materials, the problem of poor compatibility between plant materials and polymer materials is solved, and the high dispersion and mechanical properties are improved, providing a highly efficient wood Method for preparing composite materials.
Patent Information
- Application Number
- CN202310000395.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-03
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-01-03
AI Technical Summary
Among the existing wood-plastic materials, plant-based materials have poor compatibility with polymer materials, resulting in poor dispersion and reduced mechanical properties.
Strongly polar branched polyolefins are used as additives to enhance the interface binding force by reacting with thermoplastic polyurethane elastomers, promote uniform dispersion of plant powders, and improve dispersion ability by reducing cohesion and enhance mechanical properties.
It significantly improves the compatibility and dispersion ability of plant powder in composite materials, reduces the production of defective products, enhances the mechanical properties of composite materials, and has a unique wooden effect and low cost.
Smart Images

Figure BDA0004034240490000071 
Figure BDA0004034240490000081 
Figure BDA0004034240490000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and in particular relates to a high-dispersion wood-plastic thermoplastic polyurethane elastomer material and a preparation method thereof. Background Art
[0002] As humans pay more and more attention to environmental pollution, the market share of bio-based materials is gradually increasing. Among them, wood-plastic materials are one of the most popular bio-based materials. Wood-plastic materials not only have the characteristics of natural plants, but also can make polymer materials present the appearance of plant texture. It has the advantages of UV resistance, waterproof, insect resistance, acid and alkali resistance, corrosion resistance, easy processing, high plasticity and recyclability. It can replace almost all types of wood products and has been widely used in building materials, furniture, packaging materials, handicrafts, daily necessities, toys, home appliances, industry, automobiles, electronic products, sports goods and office supplies.
[0003] Wood plastic composite material is a low-carbon, environmentally friendly, recyclable and long-life material. Its plant raw material source is very broad, low-priced and renewable. The use of this material can reduce the use of oil and reduce the consumption of wood resources.
[0004] In the preparation of wood-plastic composite materials, since natural plant raw materials have strong polarity and hydrophilicity, while polymer materials are non-polar and non-hydrophilic, there are problems of poor compatibility and low interfacial adhesion between plant materials and polymer materials. Therefore, combining polar plant materials and non-polar polymer materials will result in poor dispersion of the two and reduced mechanical properties of the materials.
[0005] CN101747640A discloses modified plant powder of wood plastic and a preparation method thereof. The patent does not improve the problem of poor compatibility between plant materials and polymer materials, so the dispersion problem is not solved to the greatest extent.
[0006] CN110682636A discloses an elastic surface co-extruded wood-plastic profile and a preparation method thereof. The polyethylene used in the patent is a non-polar substance and is incompatible with other polar substance components, so the material has a problem of poor dispersion.
[0007] It can be seen that the existing wood-plastic material preparation technology has the problems of poor compatibility and poor dispersion between plant materials and non-polar polymer materials. Summary of the invention
[0008] In order to achieve the above technical requirements, the present invention provides a highly dispersed wood-plastic thermoplastic polyurethane elastomer material, which has good dispersibility, a simple and controllable production process, and a unique wood effect.
[0009] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is as follows:
[0010] A high-dispersion wood-plastic thermoplastic polyurethane elastomer material comprises the following components: thermoplastic polyurethane elastomer, 25-97.92%, preferably 35-93.95%, more preferably 40-88.92%; strongly polar branched polyolefin, 2-25%, preferably 4-20%, more preferably 6-18%; lubricant, 0.03-10%, preferably 0.05-8%, more preferably 0.08-6%; plant powder, 0.05-40%, preferably 2-35%, more preferably 5-30%, calculated based on the total mass of the polyurethane elastomer material.
[0011] In the present invention, the strongly polar branched polyolefin adopts a highly polar macromolecular polymer having a large number of polar functional groups as a highly polar auxiliary agent, and under the synergistic effect of a compatibilizer, the non-polar branched polyolefin and the highly polar auxiliary agent are fully wetted, so that the highly polar auxiliary agent is uniformly dispersed in the branched polyolefin, and the interfacial bonding force between the two is enhanced, thereby obtaining a strongly polar branched polyolefin with uniform internal and external polarity, and its polarity can be stably retained for a long time. At the same time, the wood filler reacts with the amide group and the styrene group in the strongly polar branched polyolefin, and the thermoplastic polyurethane elastomer reacts with the organic functional groups such as the alkyl, epoxy and vinyl groups in the strongly polar branched polyolefin, and the strongly polar branched polyolefin plays a connecting role between the plant powder and the thermoplastic polyurethane elastomer, and promotes the dispersion of the plant powder in the composite material by reducing the interfacial energy between the two phases; at the same time, the strongly polar branched polyolefin reduces the cohesion between the plant powders and further improves the dispersibility of the plant powder in the thermoplastic polyurethane elastomer matrix. The production of defective products such as flow marks, pits, and uneven dispersion is reduced. In addition, by adding strongly polar branched polyolefins, the mechanical entanglement between the thermoplastic polyurethane elastomer molecular chain and the plant powder can be strengthened, and the interface affinity between the two can be enhanced, thereby improving the mechanical properties of the composite material.
[0012] In the present invention, the thermoplastic polyurethane elastomer is one or more of conventional polyester thermoplastic polyurethane elastomer, polyether thermoplastic polyurethane elastomer, polycarbonate thermoplastic polyurethane elastomer and polycaprolactone thermoplastic polyurethane elastomer; preferably polyester thermoplastic polyurethane elastomer and / or polyether thermoplastic polyurethane elastomer; preferably, the hardness of the thermoplastic polyurethane elastomer is Shore A65-Shore D80, preferably Shore A70-Shore D70.
[0013] In the present invention, the highly polar branched polyolefin comprises a branched polyolefin, a highly polar auxiliary agent, and a compatibilizer; preferably, the branched polyolefin is selected from one or more of branched polyethylene, branched polypropylene, branched polybutene, branched polypentene, branched polyhexene, branched polyoctene, and branched polycycloolefin; preferably, the melting point of the branched polyolefin is 100-250°C; more preferably, the molecular weight of the branched polyolefin is 200-20.0×10 4 , molecular weight distribution is 1.0-4.0; preferably, the strong polar auxiliary agent is one or more of amidated polyolefin, sodium 2-acrylamido-2-methylpropane sulfonate, and sodium polystyrene sulfonate; preferably, the compatibilizer is a polyolefin ester epoxy resin, preferably one or more of polyethylene ester epoxy resin, polypropylene ester epoxy resin, and styrene ester epoxy resin; preferably, in the strong polar branched polyolefin, the branched polyolefin is 60-97 parts, the polar auxiliary agent is 1-20 parts, and the compatibilizer is 2-20 parts.
[0014] In the present invention, the preparation method of the highly polar branched polyolefin is: firstly, the branched polyolefin, polar auxiliary agent and compatibilizer are mixed to obtain a premix, and then the premix is added to a twin-screw extruder for granulation or added to an internal mixer for internal mixing, granulation and drying.
[0015] In the present invention, the lubricant is one or more of polyethylene wax, oxidized polyethylene wax, ethylene-vinyl acetate wax, vinyl bisstearamide wax, calcium stearate, and zinc stearate.
[0016] In the present invention, the plant powder is selected from one or more of powders of plant skins, plant roots, plant stems, plant leaves, fruit shells, fruit peels, and fruit cores, and the thermal degradation temperature of the plant powder under a nitrogen atmosphere is ≥190°; preferably, the plant powder is selected from one or more of powders of bark, tree trunks, leaves, rice husks, straws, and nut shells, and the thermal degradation temperature of the plant powder under a nitrogen atmosphere is ≥220°; preferably, the plant powder has a particle size of 1-2000 μm, preferably 10-500 μm; preferably, the plant powder has a moisture content of 0-5%, preferably 0-2%, based on the total mass of the plant powder.
[0017] Another object of the present invention is to provide a method for preparing a highly dispersed wood-plastic thermoplastic polyurethane elastomer material.
[0018] A method for preparing the above-mentioned high-dispersion wood-plastic thermoplastic polyurethane elastomer material, the method comprising the following steps:
[0019] S1: uniformly mixing the molten strongly polar branched polyolefin and the plant powder, and crushing them after cooling to obtain a crushed material of the plant powder coated with the strongly polar branched polyolefin;
[0020] S2: mixing the thermoplastic polyurethane elastomer, the crushed material of the strongly polar branched polyolefin coated plant powder, and the lubricant to obtain a premix;
[0021] S3: Add the premix into an extruder for extrusion granulation and drying to obtain the target product.
[0022] In the present invention, the melting temperature described in S1 is 150-240°C.
[0023] In the present invention, the mixing in S2 is performed using a high speed mixer, preferably with a mixing speed of 30-400 rpm and a mixing time of 3-30 min.
[0024] In the present invention, the extruder described in S3 is a single screw and / or a twin screw.
[0025] Compared with the prior art, the beneficial effects of the present invention are:
[0026] (1) Effectively improve the compatibility of plant powder and composite materials, and promote the dispersion of plant powder in composite materials; at the same time, the strong polar branched polyolefin reduces the cohesion between plant powders and further improves the compatibility and dispersion of plant powder in the thermoplastic polyurethane elastomer matrix. It greatly reduces the occurrence of defective products such as flow marks and uneven dispersion in the production of finished products.
[0027] (2) It can enhance the interfacial affinity between thermoplastic polyurethane elastomer and plant powder, and improve the mechanical properties of the composite material by more than 80%.
[0028] (3) The plant powder in the raw materials is a natural renewable resource with biodegradability. The composite material obtained can be recycled and has less pollution to the environment. At the same time, it reduces the consumption of non-renewable resource petroleum, reduces the consumption of manpower and resources, and saves energy and reduces emissions.
[0029] (4) The prepared material is a unique spray-free material with low cost and high simulation, which greatly improves the innovation and diversity of the appearance of thermoplastic polyurethane elastomer products and brings greater development space for product design. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the SEM characterization result of Comparative Example 1;
[0031] Figure 2 This is the SEM characterization result of Comparative Example 2;
[0032] Figure 3 This is the SEM characterization result of Example 3;
[0033] Figure 4 This is the SEM characterization result of Example 4. DETAILED DESCRIPTION
[0034] The present invention is further described below in conjunction with embodiments. The following examples are only used as illustrations of the present invention and are not intended to limit the scope of the present invention.
[0035] The polyester or polyether thermoplastic polyurethane elastomers were purchased from Wanhua Chemical Group Co., Ltd.: polyester thermoplastic polyurethane elastomer WHT-1185, polyether thermoplastic polyurethane elastomer WHT-8170, polycaprolactone thermoplastic polyurethane elastomer WHT-2198.
[0036] The highly polar additives were purchased from BASF's polyacrylamide Zetag8140 (effective content ≥ 94%), Condis Chemical's sodium 2-acrylamido-2-methylpropane sulfonate (purity 99%), and Beijing Hailiyang Chemical Technology Co., Ltd.'s sodium polystyrene sulfonate (purity 99%).
[0037] The compatibilizer was purchased from vinyl epoxy resin (active ingredient content ≥ 90%) from Yixing Yanglin New Materials Co., Ltd.
[0038] The lubricant was purchased from BASF's ethylene-vinyl acetate wax EVA3 (active substance content 25%) and Klein's polyethylene wax 3620 (active substance content 99.9%).
[0039] Plant powders were purchased from poplar powder (particle size 80 mesh, mud content 0.01%, water content 0.01%) from Lingshou County Rijin Mineral Products Processing Plant, corn straw powder (particle size 200 mesh) from Xi'an Jihe Agricultural Technology Co., Ltd., and walnut shell powder (particle size 300 mesh) from Hebei Kexu Building Materials Co., Ltd.
[0040] The branched polyolefins were purchased from polyethylene YLF-1801 from Sinopec Yangzi Petrochemical Co., Ltd., polyisobutylene N50 from BASF, and polypropylene K8003 from Sino-Korea (Wuhan) Petrochemical Co., Ltd.
[0041] Example 1
[0042] The preparation steps and dosage of each component are as follows
[0043] (1) According to weight proportions, 0.2 kg of a strong polar auxiliary agent, 2-acrylamide-2-methylpropane sulfonate sodium, 1 kg of a compatibilizer, and 2 kg of polyisobutylene N50 were added to a mixer and mixed evenly to obtain a premix;
[0044] (2) adding the premix obtained in step (1) to a twin-screw extruder for granulation, or adding it to an internal mixer for internal mixing and granulation, and drying to obtain a highly polar branched polyolefin;
[0045] (3) The strongly polar branched polyolefin is heated to a molten state at a heating temperature of 170° C. 3.2 kg of the molten strongly polar branched polyolefin is uniformly mixed with 20 kg of poplar powder, and the mixture is cooled and then crushed to obtain a crushed material of the strongly polar branched polyolefin-coated plant powder.
[0046] (4) Add 76.75 kg of WHT-2198, 22.2 kg of crushed material of strongly polar branched polyolefin-coated plant powder, and 0.05 kg of lubricant ethylene-vinyl acetate wax EVA3 into a high-speed mixer, and mix for 3 minutes at a speed of 100 rpm to obtain a premix;
[0047] (5) Add the premix obtained in step (4) into a single-screw / twin-screw extruder for extrusion granulation.
[0048] Embodiment 2-7
[0049] The preparation steps of Examples 2-7 are carried out according to Example 1, and the process parameters and the amounts of each component used in the examples are as follows:
[0050] Table 1
[0051]
[0052]
[0053] Example Example 5 Example 6 Example 7 WHT-1185 93.65kg 72.5kg 41.8kg Sodium 2-acrylamido-2-methylpropane sulfonate 0.05kg 2.5kg 4.2kg Polyvinyl ester epoxy resin 0.1kg 2kg 4kg Polyethylene YLF-1801 —— 6kg 15kg Polypropylene K8003 5kg —— —— Poplar powder 1kg 15kg 35kg Ethylene vinyl acetate wax EVA3 0.2kg 2kg 8kg Step 3 Heating Temperature 230℃ 150℃ 200℃ Step 4 Speed 150rpm 170rpm 120rpm Step 4 Mixing time 10min 20min 30min
[0054] Comparative Example 1
[0055] According to weight proportions, 2 kg of sodium polystyrene sulfonate as a strong polar auxiliary agent and 3 kg of polyvinyl ester epoxy resin as a compatibilizer are added to a mixer and mixed evenly to obtain a premix. The premix is then evenly mixed with 20 kg of walnut shell powder, and then added to a high-speed mixer together with 73 kg of thermoplastic polyurethane elastomer and 2 kg of lubricant ethylene-vinyl acetate wax. The mixture is mixed at a speed of 30 rpm for 15 minutes to obtain a premix. The premix obtained in step (4) is added to a single-screw / twin-screw extruder for extrusion granulation.
[0056] Comparative Example 2
[0057] According to the weight proportion, 2kg of compatibilizer polyvinyl ester epoxy resin and 15kg of polyethylene YLF-1801 are added to the mixer, mixed evenly to obtain a premix; the obtained premix is added to a twin-screw extruder for granulation, or added to a banbury mixer for banburying and granulation, and then dried to obtain a strongly polar branched polyolefin; the strongly polar branched polyolefin is heated to a molten state at a heating temperature of 240°C, 17kg of the molten strongly polar branched polyolefin is uniformly mixed with 20kg of poplar powder, and then pulverized after cooling to obtain a crushed material of strongly polar branched polyolefin-coated plant powder. 62.2kg of thermoplastic polyurethane elastomer, 37kg of crushed material of strongly polar branched polyolefin-coated plant powder, and 0.8kg of lubricant ethylene-vinyl acetate wax are added to a high mixer, and the speed is 300 rpm, mixed for 20 minutes to obtain a premix; the obtained premix is added to a single screw / twin screw extruder for extrusion granulation.
[0058] The process parameters and dosage of each component of Comparative Example 1-2 are as follows:
[0059] Table 2
[0060] Comparative Example Comparative Example 1 Comparative Example 2 WHT-1185 73kg 62.2kg Poplar powder —— 20kg Walnut shell powder 20kg —— Ethylene vinyl acetate wax EVA3 2kg 0.8kg Polyvinyl ester epoxy resin 3kg 2kg Polyethylene YLF-1801 —— 15kg Sodium polystyrene sulfonate 2kg —— Step 3 Heating Temperature —— 240℃ Step 4 Speed 30rpm 300rpm Step 4 Mixing time 15min 20min
[0061] The performance test methods of Examples 1-7 and Comparative Examples 1-2 are as follows, and the test results are shown in Table 3.
[0062] Flow marks: Use an injection molding machine (injection molding machine model: injection molding machine MA600 of Haitian Plastic Machinery Group Co., Ltd.) to inject the material into a 80mm*80mm*2mm sample, and visually observe the flow marks on the front and back of the sample;
[0063] Dispersion: Use a tablet press (tablet press model: manual tablet press HG-3621 of Hengguang Technology Co., Ltd.) to press the material into a disc with a diameter of 200 mm and a thickness of 0.5 mm. Detect the number of agglomerated particles on the disc, and the size of the agglomerated particles is ≥0.1 mm;
[0064] Mechanical properties test: tensile strength rate refers to ASTM D412, elongation at break refers to ASTM D624, instrument model is AZS-X of Shimadzu Instrument Co., Ltd.;
[0065] Electron microscope: Cut the injection molded sample for flow mark measurement and measure the cross-sectional dispersion. The instrument model is SU8010 from Hitachi.
[0066] Table 3
[0067]
[0068] From the test results of the embodiments and comparative examples in Table 3 above, it can be seen that embodiments 1-7 use strongly polar branched polyolefins, plant powders and thermoplastic polyurethane elastomers, and comparative examples 1-2 use plant powders without adding branched polyolefins or strongly polar additives and thermoplastic polyurethane elastomers. By comparing embodiments 1-7 and comparative examples 1-2, it is found that the plant powders in the products obtained by adding strongly polar branched polyolefins to the wood-plastic thermoplastic polyurethane elastomer are well dispersed, have no flow marks, and have better mechanical properties.
[0069] Comparative Example 1 is compared with Example 3, the difference is that Comparative Example 1 does not add branched polyolefin, and the electron microscopy test results of Comparative Example 1 have undispersed agglomerates. The test results in Table 3 show that the material prepared in Example 3 is better dispersed than that in Comparative Example 1, has no flow marks, and has better mechanical properties.
[0070] Compared with Example 4, Comparative Example 2 is different in that no strong polar additive is added to Comparative Example 2. The electron microscope test results show that Comparative Example 2 has undispersed agglomerates. The test results in Table 3 show that the material prepared in Example 4 is better dispersed than that in Comparative Example 1, has no flow marks, and has better mechanical properties.
Claims
1. A highly dispersed wood-plastic thermoplastic polyurethane elastomer material, characterized in that: The material comprises the following components: Thermoplastic polyurethane elastomer, 25-97.92%; Strongly polar branched polyolefins, 2-25%; Lubricant, 0.03-10%; Plant powder, 0.05-40%; Measured by the total mass of polyurethane elastomer material; The highly polar branched polyolefin comprises branched polyolefin, a highly polar auxiliary agent, and a compatibilizer; the highly polar auxiliary agent is one or more of amidated polyolefin, sodium 2-acrylamide-2-methylpropane sulfonate, and sodium polystyrene sulfonate; and the compatibilizer is a polyolefin ester epoxy resin.
2. The polyurethane elastomer material according to claim 1, characterized in that: The material comprises the following components: Thermoplastic polyurethane elastomer, 35-93.95%; Strongly polar branched polyolefins, 4-20%; Lubricant, 0.05-8%; Plant powder, 2-35%; Measured based on the total mass of polyurethane elastomer material.
3. The polyurethane elastomer material according to claim 2, characterized in that: The material comprises the following components: Thermoplastic polyurethane elastomer, 40-88.92%; Strongly polar branched polyolefins, 6-18%; Lubricant, 0.08-6%; Plant powder, 5-30%; Measured based on the total mass of polyurethane elastomer material.
4. The polyurethane elastomer material according to claim 1, characterized in that: The thermoplastic polyurethane elastomer is one or more of conventional polyester thermoplastic polyurethane elastomer, polyether thermoplastic polyurethane elastomer, polycarbonate thermoplastic polyurethane elastomer and polycaprolactone thermoplastic polyurethane elastomer.
5. The polyurethane elastomer material according to claim 4, characterized in that: The thermoplastic polyurethane elastomer is a polyester thermoplastic polyurethane elastomer and / or a polyether thermoplastic polyurethane elastomer; The hardness of the thermoplastic polyurethane elastomer is Shore A65-Shore D80.
6. The polyurethane elastomer material according to claim 5, characterized in that: The hardness of the thermoplastic polyurethane elastomer is Shore A70-Shore D70.
7. The polyurethane elastomer material according to claim 1, characterized in that: The branched polyolefin is selected from one or more of branched polyethylene, branched polypropylene, branched polybutene, branched polypentene, branched polyhexene, branched polyoctene, and branched polycycloolefin; The compatibilizer is one or more of polyvinyl ester epoxy resin, polypropylene ester epoxy resin, and styrene ester epoxy resin; In the highly polar branched polyolefin, the branched polyolefin accounts for 60-97 parts, the polar auxiliary agent accounts for 1-20 parts, and the compatibilizer accounts for 2-20 parts.
8. The polyurethane elastomer material according to claim 7, characterized in that: The branched polyolefin has a melting point of 100-250°C.
9. The polyurethane elastomer material according to claim 8, characterized in that: The molecular weight of the branched polyolefin is 200-20.0×10 4 , the molecular weight distribution is 1.0~4.
0.
10. The polyurethane elastomer material according to claim 1, characterized in that: The preparation method of the highly polar branched polyolefin is as follows: firstly, the branched polyolefin, the polar auxiliary agent and the compatibilizer are mixed to obtain a premix, and then the premix is added to a twin-screw extruder for granulation or added to an internal mixer for internal mixing, granulated and dried.
11. The polyurethane elastomer material according to claim 1, characterized in that: The lubricant is one or more of polyethylene wax, oxidized polyethylene wax, ethylene-vinyl acetate wax, vinyl bisstearamide wax, calcium stearate, and zinc stearate.
12. The polyurethane elastomer material according to claim 1, characterized in that: The plant powder is selected from one or more of powders of plant skins, plant roots, plant stems, plant leaves, fruit shells, fruit peels, and fruit cores, and the thermal degradation temperature of the plant powder under nitrogen atmosphere is ≥190°.
13. The polyurethane elastomer material according to claim 12, characterized in that: The plant powder is selected from one or more of powders of bark, trunk, leaves, rice husk, straw, and nut shell, and the thermal degradation temperature of the plant powder under nitrogen atmosphere is ≥220°; The particle size of the plant powder is 1-2000 μm; The water content of the plant powder is 0-5%, based on the total mass of the plant powder.
14. The polyurethane elastomer material according to claim 13, characterized in that: The plant powder has a particle size of 10-500 μm; The water content of the plant powder is 0-2%, based on the total mass of the plant powder.
15. A method for preparing the highly dispersed wood-plastic thermoplastic polyurethane elastomer material according to any one of claims 1 to 14, characterized in that: The method comprises the following steps: S1: uniformly mixing the molten strongly polar branched polyolefin and the plant powder, and crushing them after cooling to obtain a crushed material of the plant powder coated with the strongly polar branched polyolefin; S2: mixing the thermoplastic polyurethane elastomer, the crushed material of the strongly polar branched polyolefin coated plant powder, and the lubricant to obtain a premix; S3: Add the premix into an extruder for extrusion granulation and drying to obtain the target product.
16. The method according to claim 15, characterized in that The melting temperature of S1 is 150-240°C; And / or, the mixing in S2 adopts a high-speed mixer; And / or, the extruder in S3 is a single screw and / or a twin screw.
17. The method according to claim 16, characterized in that S2 mixing speed 30-400rpm, mixing time 3-30min.
Citation Information
Patent Citations
Modified plant powder for wood-plastics and preparation method and application thereof
CN101747640A
Elastic surface co-extruded wood-plastic profile and preparation method thereof
CN110682636A
Polyolefin wood-plastic composite and preparation method thereof
CN103819801A
Preparation method of polyurethane toughening PE wood-plastic composite material
CN104927381A